Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To simplify the expression \(-2i \sqrt{-12}\), follow these steps:
1. Break Down the Square Root of the Negative Number:
Recognize that \( \sqrt{-12} \) can be broken down as \( \sqrt{12 \cdot -1} \). This can be further simplified using the property of square roots:
[tex]\[ \sqrt{12 \cdot -1} = \sqrt{12} \cdot \sqrt{-1} \][/tex]
2. Simplify the Imaginary Unit:
Recall that \( \sqrt{-1} \) is defined as \( i \). So,
[tex]\[ \sqrt{-12} = \sqrt{12} \cdot i \][/tex]
3. Substitute Back into the Expression:
Substitute \( \sqrt{-12} = \sqrt{12} \cdot i \) back into the original expression:
[tex]\[ -2i \sqrt{-12} = -2i (\sqrt{12} \cdot i) \][/tex]
4. Combine Like Terms:
When you multiply \( -2i \) and \( \sqrt{12} \cdot i \), you focus first on multiplying the imaginary units:
[tex]\[ -2i \cdot i \cdot \sqrt{12} \][/tex]
Given that \( i \cdot i = i^2 \), and knowing that \( i^2 = -1 \):
[tex]\[ -2i^2 \cdot \sqrt{12} = -2 \cdot (-1) \cdot \sqrt{12} = 2 \cdot \sqrt{12} \][/tex]
5. Simplify the Radicand:
The term \( \sqrt{12} \) can be further simplified by recognizing that \( 12 = 4 \cdot 3 \), and \( 4 \) is a perfect square:
[tex]\[ \sqrt{12} = \sqrt{4 \cdot 3} = \sqrt{4} \cdot \sqrt{3} = 2\sqrt{3} \][/tex]
6. Combine All Parts:
Substitute \( \sqrt{12} = 2\sqrt{3} \) back into the expression \( 2 \cdot \sqrt{12} \):
[tex]\[ 2 \cdot \sqrt{12} = 2 \cdot 2\sqrt{3} = 4\sqrt{3} \][/tex]
So, the simplified form of the expression \(-2i \sqrt{-12}\) is:
[tex]\[ 4\sqrt{3} \][/tex]
1. Break Down the Square Root of the Negative Number:
Recognize that \( \sqrt{-12} \) can be broken down as \( \sqrt{12 \cdot -1} \). This can be further simplified using the property of square roots:
[tex]\[ \sqrt{12 \cdot -1} = \sqrt{12} \cdot \sqrt{-1} \][/tex]
2. Simplify the Imaginary Unit:
Recall that \( \sqrt{-1} \) is defined as \( i \). So,
[tex]\[ \sqrt{-12} = \sqrt{12} \cdot i \][/tex]
3. Substitute Back into the Expression:
Substitute \( \sqrt{-12} = \sqrt{12} \cdot i \) back into the original expression:
[tex]\[ -2i \sqrt{-12} = -2i (\sqrt{12} \cdot i) \][/tex]
4. Combine Like Terms:
When you multiply \( -2i \) and \( \sqrt{12} \cdot i \), you focus first on multiplying the imaginary units:
[tex]\[ -2i \cdot i \cdot \sqrt{12} \][/tex]
Given that \( i \cdot i = i^2 \), and knowing that \( i^2 = -1 \):
[tex]\[ -2i^2 \cdot \sqrt{12} = -2 \cdot (-1) \cdot \sqrt{12} = 2 \cdot \sqrt{12} \][/tex]
5. Simplify the Radicand:
The term \( \sqrt{12} \) can be further simplified by recognizing that \( 12 = 4 \cdot 3 \), and \( 4 \) is a perfect square:
[tex]\[ \sqrt{12} = \sqrt{4 \cdot 3} = \sqrt{4} \cdot \sqrt{3} = 2\sqrt{3} \][/tex]
6. Combine All Parts:
Substitute \( \sqrt{12} = 2\sqrt{3} \) back into the expression \( 2 \cdot \sqrt{12} \):
[tex]\[ 2 \cdot \sqrt{12} = 2 \cdot 2\sqrt{3} = 4\sqrt{3} \][/tex]
So, the simplified form of the expression \(-2i \sqrt{-12}\) is:
[tex]\[ 4\sqrt{3} \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.